The archaeology of cult in the Ancient Near East: methodology and practice - Gilmour, Garth (Old Testament essays, 2000)
A review of the research on the archaeology of cult in early Iron Age Palestine has shown the need for a critical theoretical framework for dealing with the study of cult in archaeological contexts. The task is to approach the archaeology of religion in this region in a way that is both scientific, and therefore testable, and interpretive, and therefore allows for an understanding of cultic remains as representations both of symbolic attitudes and actions which took place largely in the minds of the people that created them, and of the wider social context. Such an approach allows for both the application of a strict methodology to the excavated features and artefacts, and the incorporation of data crucial to the interpretation of cultic remains such as comparative texts, archaeological context, space/time correlates and anthropological research. This requires both a nomothetic approach that uses a defined set of rules in initial interpretation, and a cognitive-processual approach that uses as wide a selection of comparative material as possible to interpret the individual and societal attitudes, beliefs and pressures that created the data under review. An example of such a methodology is presented for evaluation, and its application to excavated material from the Iron Age I period is briefly discussed.